NLO corrections to the pair production of supersymmetric particles - Obikhod, T.V.; Verbytskyy, A.A. (Вопросы атомной науки и техники, 2014)
The analysis of recent experimental data received from LHC (CMS) restricts the range of MSSM parameters. Using computer programs SOFTSUSY, SDECAY the mass spectrum and partial width of superpatners are calculated. With the help of computer program PROSPINO the calculations of the next-to-leading order (NLO) corrections to the production cross sections of superpartners are made. With the help of computer program PYTHIA the NLO corrections on differential distributions of pT and η for squarks and gluino are represented. Анализ последних экспериментальных данных, полученных из БАК (КМС), ограничил пространство МССМ параметров. С помощью компьютерных программ SOFTSUSY, SDECAY посчитаны спектры масс и ширины распадов суперчастиц. Проведены расчеты next-to-leading order (NLO) поправок к поперечному сечению образования суперчастиц с помощью компьютерной программы PROSPINO. Представлены NLO поправки к дифференциальному сечению распределения по pT и η для скварков и глюино. Аналiз останнiх експериментальних даних отриманих на ВАК (КМС) звузив простiр МССМ параметрiв. За допомогою комп'ютерних програм SOFTSUSY, SDECAY розраховано спектри мас i ширини розпадiв суперчастинок. Проведено розрахунки next-to-leading order (NLO) поправок до поперечного перерiзу утворення суперчастiнок за допомогою комп'ютерної програми PROSPINO. Представлено NLO поправки до диференцiйного перерiзу розподiлу по pT i η для скваркiв i глюiно.